Chordoma of the thoracic and lumbosacralis spine with recurrence and locally invasive process – case report - Ziółkowska, Ewa; Biedka, Marta; Mross, Mariusz; Makarewicz, Roman (Contemporary Oncology/Współczesna Onkologia, 2007)
Chordomas are uncommon tumours, accounting for 2-4% of all primary malignant bone tumours. The location of the tumours in decreasing frequency is: the sacrococcygeal region, 50%; spheno-occipital region, 30-40%; and other spinal segments, 15%. Most patients are aged from 40 to 70 years. The standard therapy is radical resection. Local recurrence rate of sacrococcygeal chordomas after surgery is about 46-70% and prevalence of metastasis is 10-43%. The median times to recurrence after surgery are 3.4 years for radical resection and 8 months for subtotal excision. High-dose radiation is increasingly used in combination with surgery for non-resectable lesions. Chordoma has a low sensitivity to chemotherapy. The purpose of our work is to show a very rare case of chordoma of the thoracic and lumbosacral spine with recurrence and locally invasive process in a 59-year-old woman and demonstrate our experience from adjusted diagnostic workup and approach of treatment.